Promoting Physical Activity in the Management of Type 2 Diabetes: A Feasibility Study to Develop Intervention Tools for Delivery of Diabetes‐Specific Education - Daniel Crabtree; Sara Bradley; Jenni Connelly; Lynn Bauermeister; Trish Gorely; Sandra MacRury (Lifestyle Medicine)
ABSTRACT Background Physical activity is an important aspect of lifestyle management and type 2 diabetes, although the percentage of people with type 2 diabetes achieving recommended guidelines is low. Supported self‐management underpinned by group educational programmes may be helpful but difficult to implement in remote and rural areas. We aimed to test the feasibility of an approach based on education delivered individually by community‐based exercise advisors to people with type 2 diabetes. Methods Following the development of an online educational toolkit a mixture of exercise advisors and people with type 2 diabetes were recruited. People with diabetes had a face‐to‐face consultation with an exercise advisor with mutually agreed follow‐up over 6 months. To track physical activity, people with diabetes aimed to wear an accelerometer device for 7 days at baseline, 3 months and 6 months. Post‐intervention semi‐structured interviews were undertaken with both groups of participants to gauge perspectives of the initiative. Results There was a 56% total attrition rate from baseline to 3 months due to COVID‐19 and its impact on clinical research. Around 50% of participants achieved minimum physical activity recommendations at each time point and 22% of participants had accelerometer data at 3 time points. People with diabetes valued interaction with exercise advisors and felt that the programme would be of greatest benefit to less active individuals. Exercise advisors felt that the programme provided more opportunities and increased confidence and that training in working with older less active individuals would be useful for them. Conclusion It is feasible to develop a physical activity programme delivered by non‐healthcare practitioners underpinned by diabetes‐specific education tailored to people with type 2 diabetes. Several project adaptions should be considered for progress to a pilot study to assess an integrated physical activity programme delivered by community exercise advisors.